Starch-carrageenan interactions in aqueous media: Role of each polysaccharide chemical and macromolecular characteristics. (May 2017) - Lascombes, C.; Agoda-Tandjawa, G.; Boulenguer, P.; Le Garnec, C.; Gilles, M.; Mauduit, S.; Barey, P.; Langendorff, V.
Abstract: In this study, physico-chemical interactions between carrageenan chains and starch granules were investigated through methylene blue spectrophotometric method by considering the chemical and macromolecular characteristics of each polysaccharide. For that purpose, various proportions of κ-, ι- or λ- carrageenan and different types of starches (native, chemically modified, "deproteinated" or not) were used. Blue dextran spectrophotometric method was also developed to evaluate the quantity of water absorbed by starch granules and hereby their swelling behavior allowing to determine the accurate amount of trapped carrageenan. It was demonstrated that the interactions between starch granules and carrageenan chains are not strongly impacted by starch chemical modifications. However, experiments with "deproteinated" starch showed that starch endogenous proteins can play a part in starch-carrageenan interactions. Three coexisting phenomena were found to occur when starch is pasted together with carrageenan. That consisted in: (i) partial penetration of carrageenan in starch granules, (ii) partial "exclusion" of carrageenan by starch granules and (iii) a predominant adsorption of carrageenan on starch granules due mainly to osmotic pressure effect. Moreover, the electrostatic interactions between starch endogenous proteins and carrageenan chains played a minor role. As expected, the interaction level appeared to be strongly depending from the carrageenan charge density: the lower the charge, the higher the interaction between starch and carrageenan, independently from starch chemical characteristics. Furthermore, it seemed that the rheological properties of the mixed systems are preferentially driven by the partial "exclusion" phenomenon as well as the role of starch granules as "filler". Graphical abstract: Highlights: Methylene blue spectrophotometry allows to quantify starch-carrageenan interactions. Starch endogenous proteins play a minor role in starch-carrageenan interactions. Starch-carrageenan interactions are not strongly impacted by starch chemical modifications. The lower carrageenan charge density, the higher the interaction between starch and carrageenan.